Prognostic significance of histological therapeutic effect in preoperative chemotherapy for breast cancer. Issue 1 (27th November 2015) - Kobayashi, Kokoro; Horii, Rie; Ito, Yoshinori; Miyagi, Yumi; Ohno, Shinji; Iwase, Takuji; Akiyama, Futoshi
Abstract : To establish a prognostic prediction system, we examined the relationships between prognosis and histological therapeutic effect or ypTNM classification in 258 breast cancer patients who received neoadjuvant chemotherapy. The case distribution according to therapeutic effect was nine patients (3.5%) with Grade 0, 169 (65.5%) with Grade 1, 58 (22.5%) with Grade 2, and 22 (8.5%) with Grade 3. The 5‐year overall survival (OS) rate by therapeutic effect was 56% in Grade 0, 81% in Grade 1, 87% in Grade 2, and 96% in Grade 3. The higher the therapeutic effect the better the prognosis, with a significant difference among the groups ( P = 0.008). The case distribution according to ypTNM classification was 20 patients (7.8%) with Stage 0, 83 (32.2%) with Stage I, 77 (29.8%) with Stage II, and 78 (30.2%) with Stage III. The 5‐year OS rate by ypTNM classification was 95% in Stage 0, 94% in Stage I, 89% in Stage II, and 59% in Stage III. While prognosis was mostly comparable in Stages 0 and I, in the other stages it became significantly worse as residual cancer increased ( P < 0.001). The prognosis of breast cancer patients with neoadjuvant chemotherapy can be predicted by histological therapeutic effect and staging classification of residual cancer.